Analisis Balik Kestabilan Lereng Highwall di Pit Pandu PT. Putra Muba Coal Kabupaten Musi Banyuasin Provinsi Sumatera Selatan - Andy Yanottama; Muhammad Faisal Seprizal; Jarot Wiratama; Zella Navtalia; Leta Lestari (Pusat riset dan Inovasi Nasional, 2025)
Putra Muba Coal is one of the subsidiaries under the MNC Group, operating in the coal mining sector with an IUP (Mining Business Permit) area covering 2,947 hectares. During its mining operations at the Pandu Pit, PT. Putra Muba Coal experienced a landslide incident on the highwall side. Therefore, a back-analysis using the deterministic method was conducted to determine the material property values that led to the slope failure in the mining area. The slope material consists of claystone and siltstone layers, each with a cohesion value of 192.3 kN/m² and 157.0 kN/m², and internal friction angles of 25.3° and 24.4°, respectively. Based on the back-analysis results, it was found that there was a decrease in material property values, with cohesion reduced by 91% and the internal friction angle reduced by 29%. This reduction in material properties suggests that the decrease in cohesion was the primary factor causing the highwall slope failure, as indicated by the back-analysis of slope stability which resulted in a safety factor of (SF = 1.008).